Monolithic refractory composition for metal casting, method for manufacturing monolithic refractory composition for metal casting, and hardened product obtained by using monolithic refractory composition for metal casting
By increasing the organic fiber content and reducing the inorganic fiber content, the irregular refractory composition, combined with colloidal silicone, ion bonding agent and inorganic filler, the problem of the composition being prone to cracks after reducing the content of the fiber is solved, and the effect of sufficient bending strength and thermal retention is achieved.
Patent Information
- Application Number
- JP2023150547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
The irregular refractory compositions of existing metal casting are prone to cracks after reducing the content of organic fibers or inorganic fibers and are difficult to form sufficient bending strength.
By increasing the content of organic fibers while reducing the content of inorganic fibers, irregular refractory compositions containing colloidal silicone, ion bonding agents and inorganic fillers are used to ensure that the composition is not prone to cracks during drying or sintering, and has sufficient bending strength in practical applications.
The irregular refractory composition reduces the possibility of cracks while reducing the content of inorganic fibers and has sufficient bending strength and thermal retention in practical applications.
Smart Images

Figure 2025043179000001 
Figure 2025043179000002 
Figure 2025043179000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a castable refractory composition for metal casting which can be suitably used in areas that come into direct contact with molten metal in casting equipment for aluminum, magnesium, etc., and to a cured product of the castable refractory composition for metal casting. [Background technology]
[0002] In casting equipment for non-ferrous metals such as aluminum, insulating walls made by applying an amorphous refractory composition and then drying or firing are used as lining materials for constructing molten metal holding components that come into contact with molten metal, such as gutters, molten metal holding furnaces, and ladles. In addition to the amorphous fireproof composition, a fireproof molding is also used as the lining material, and the joints of the fireproof molding are sometimes filled with the amorphous fireproof composition and then dried or fired to form an insulating wall.
[0003] As amorphous refractory compositions for metal casting and hardened products obtained by drying or firing amorphous refractory compositions for metal casting, which are used as materials for forming refractory molded bodies for metal casting such as the above-mentioned lining materials and joint materials, there are known those containing aluminosilicate fibers as inorganic fibers, for example, as disclosed in Patent Document 1. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-093726 A Summary of the Invention [Problem to be solved by the invention]
[0005] The above-mentioned aluminosilicate fiber is an amorphous ceramic fiber also known as refractory ceramic fiber (RCF). It is an artificial mineral fiber made by mixing and blending approximately equal amounts of alumina and silica, melting them in an electric furnace, extracting them as a thin stream, and then blowing them into fibers. Since it has excellent heat resistance and is low cost, it is ideally used in various components that require fire resistance.
[0006] Meanwhile, the above-mentioned aluminosilicate fibers have recently been designated as "specified chemical substances (class 2 substances)" under the Industrial Safety and Health Act, and are now designated as fibers that require proper handling.
[0007] For this reason, there is a trend toward demands for castable refractory compositions for metal casting and their cured products in which the amount of aluminosilicate fibers used is reduced or no aluminosilicate fibers are used at all.
[0008] As an inorganic fiber that can be substituted for the aluminosilicate fiber, alumina fiber, which is known as a crystalline ceramic fiber, may be considered. However, alumina fibers are known to be expensive among inorganic fibers, and in order to use them as constituent fibers of amorphous refractory compositions for metal casting and their cured products, it is practically necessary to reduce the amount used.
[0009] Thus, it has become desirable for moldable refractory compositions for metal casting and cured products thereof to have a reduced content of inorganic fibers.
[0010] On the other hand, when the amount of inorganic fibers in the amorphous refractory composition for metal casting was reduced, cracks were likely to occur, especially in curved surfaces, when the amorphous refractory composition for metal casting was applied and dried or fired to form a hardened product.
[0011] Furthermore, it is desirable that the cured product of the moldable refractory composition for metal casting has sufficient bending strength for use as a refractory molded article for metal casting.
[0012] Therefore, the present invention aims to provide an amorphous refractory composition for metal casting that can be filled into joints and cracks in refractory moldings, or can be freely shaped by itself and dried and solidified, while reducing the content of inorganic fibers, and that is less likely to crack when dried or fired and hardened to form a hardened product having sufficient bending strength for practical use, as well as to provide a method for producing the amorphous refractory composition for metal casting and a hardened product of the amorphous refractory composition for metal casting. [Means for solving the problem]
[0013] In order to achieve the above-mentioned object, the present inventors conducted intensive research and came up with the idea of reducing the amount of inorganic fibers while increasing the amount of organic fibers in an amorphous refractory composition for metal casting.
[0014] As described above, the amorphous refractory composition for metal casting is applied and then dried or fired to form a hardened product (a refractory molded body for metal casting). However, when organic fibers are used as the constituent fibers of the amorphous refractory composition for metal casting, these organic fibers are burned away during the firing process or when the molten metal is cast, and therefore it has been thought that they are difficult to use as aggregates (reinforcing fibers) for refractory molded bodies for metal casting. For this reason, in the past, even when organic fibers were used as constituent fibers of amorphous refractory compositions for metal casting, they were required to be used in the presence of a sufficient amount of inorganic fibers, and it was not possible to reduce the amount of inorganic fibers used and use organic fibers in place of inorganic fibers.
[0015] On the other hand, after extensive research, the inventors have found that when the amount of inorganic fibers in an amorphous refractory composition for metal casting is reduced while the amount of organic fibers is increased in place of the inorganic fibers, it is possible to form a hardened product (refractory molded body for metal casting) that is not only less likely to crack when dried or fired and hardened, but also has sufficient bending strength for practical use, and have completed the present invention based on this finding.
[0016] That is, the present invention provides (1) The solid content contains 1.00 to 15.00 mass% of inorganic fibers, 1.00 to 13.00 mass% of organic fibers, colloidal silica, an ion-bonding substance, and an inorganic filler. A moldable refractory composition for metal casting, (2) The amorphous refractory composition for metal casting according to (1) above, wherein the solid content contains, in terms of silica, 2.00 to 20.00 mass% of the colloidal silica, 4.00 to 40.00 mass% of the ion-binding substance, and 30.0 to 92.00 mass% of the inorganic filler. (3) The amorphous refractory composition for metal casting according to the above (1), wherein the solid content contains 2.00 to 28.00 mass% of the inorganic fibers and the organic fibers in total. (4) The amorphous refractory composition for metal casting according to the above (1), wherein the ratio of the content of the organic fibers to the content of the inorganic fibers in the solid content is 0.18 to 3.08 by mass ratio; (5) The refractory composition for metal casting according to the above (1), wherein the inorganic fibers are alumina fibers. (6) A method for producing the castable refractory composition for metal casting described in (1) above, comprising the steps of: Inorganic fibers, organic fibers, colloidal silica, ion-bonding substances and inorganic fillers, The inorganic fibers are mixed in an amount of 1.00 to 15.00 mass % and the organic fibers are mixed in an amount of 1.00 to 13.00 mass % in the solid content. A method for producing an unshaped refractory composition for metal casting, (7) A cured product of an amorphous refractory composition for metal casting, comprising a cured product of the refractory composition for metal casting according to any one of (1) to (5) above. This provides: Effect of the Invention
[0017] According to the present invention, an amorphous refractory composition for metal casting is provided which can be filled into joints and cracks in refractory moldings, or can be freely shaped by itself and dried and solidified, while reducing the inorganic fiber content, and which is less likely to crack when dried or fired and hardened to form a hardened product having sufficient bending strength for practical use, and a hardened product of such an amorphous refractory composition for metal casting is also provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] First, the castable refractory composition for metal casting according to the present invention will be described. The amorphous refractory composition for metal casting according to the present invention contains, in its solid content, 1.00 to 15.00 mass % of inorganic fibers, 1.00 to 13.00 mass % of organic fibers, colloidal silica, an ion-bonding substance, and an inorganic filler. It is characterized by the above.
[0019] In the amorphous refractory composition for metal casting of the present invention, the inorganic fibers function as aggregates for the amorphous refractory composition, and examples thereof include one or more types selected from glass fibers, glass wool, ceramic wool, rock wool, alumina fibers, zirconia fibers, aluminosilicate fibers, biosoluble inorganic fibers, etc., with alumina fibers being particularly preferred.
[0020] In the amorphous refractory composition for metal casting according to the present invention, alumina fiber means metal oxide fiber mainly composed of alumina, which is generally referred to as alumina fiber, and as long as alumina is the main component, it may contain components such as silica and zirconia in addition to alumina. In the amorphous refractory composition for metal casting of the present invention, alumina fiber means one having an alumina content of 65 mass% or more, preferably one having an alumina content of 80 mass% or more, and preferably one having an alumina content of 90 mass% or more.
[0021] When the amorphous refractory composition for metal casting of the present invention contains alumina fibers as inorganic fibers, the proportion of alumina fibers in the total amount of inorganic fibers in the amorphous refractory composition for metal casting is preferably 10 to 100 mass%, more preferably 50 to 100 mass%, and even more preferably 100 mass% (the inorganic fibers consist only of alumina fibers).
[0022] In the amorphous refractory composition for metal casting of the present invention, the proportion of alumina fibers in the total amount of inorganic fibers satisfies the above-mentioned regulations, so that even if the content of inorganic fibers is reduced, cracks are less likely to occur when dried or fired for hardening, and a hardened product (refractory molding for metal casting) having sufficient bending strength can be easily formed.
[0023] The moldable refractory composition for metal casting according to the present invention may contain aluminosilicate fibers as inorganic fibers, but it is preferable to reduce the content as much as possible, and it is desirable to not contain aluminosilicate fibers.
[0024] In the moldable refractory composition for metal casting according to the present invention, the biosoluble inorganic fiber means an inorganic fiber having a solubility in physiological saline at 40° C. of 1% or more. An example of the biosoluble inorganic fiber is an inorganic fiber that can replace aluminosilicate fiber, such as AES fiber (alkaline earth silicate wool fiber), which is an artificial mineral fiber made from high-purity silica, calcia, and magnesia. More specifically, the biosoluble inorganic fibers include inorganic fibers described in, for example, JP 2000-220037 A, JP 2002-68777 A, JP 2003-73926 A, or JP 2003-212596 A, that is, inorganic fibers having a total content of SiO2 and CaO of 85 mass% or more, containing 0.5 to 3.0 mass% MgO and 2.0 to 8.0 mass% P2O5, and having a carcinogenicity index (KI value) of 40 or more according to the German Regulation on Hazardous Substances, inorganic fibers containing SiO2, MgO, and TiO2 as essential components, inorganic fibers containing SiO2, MgO, and manganese oxide as essential components, inorganic fibers containing 52 to 72 mass% SiO2, less than 3 mass% Al2O3, 0 to 7 mass% MgO, CaO Examples of the inorganic fibers include inorganic fibers containing 7.5 to 9.5 mass% of CdSe, 0 to 12 mass% of B2O3, 0 to 4 mass% of BaO, 0 to 3.5 mass% of SrO, 10 to 20.5 mass% of Na2O, 0.5 to 4.0 mass% of K2O, and 50 to 5 mass% of P2O, and inorganic fibers containing 75 to 80 mass% of SiO2, 19 to 25 mass% of CaO+MgO, and 1 to 3 mass% of Al2O3.
[0025] On the other hand, biosoluble inorganic fibers, including the AES fibers, dissolve in the moisture that constitutes the amorphous refractory composition for metal casting, and further react with the inorganic binder to harden, which tends to reduce the shelf life of the amorphous refractory composition for metal casting. For this reason, the amorphous refractory composition for metal casting according to the present invention may contain biosoluble inorganic fibers as inorganic fibers, but it is preferable to reduce the content as much as possible, and it is desirable to not contain biosoluble inorganic fibers.
[0026] In the moldable refractory composition for metal casting according to the present invention, the inorganic fibers preferably have an average fiber diameter of 1.0 to 50.0 μm, more preferably 1.5 to 10.0 μm, and even more preferably 2.0 to 6.0 μm. If the average fiber diameter of the inorganic fibers is less than 1.0 μm, the fibers will be prone to breakage, and the strength of the cured product (refractory molded body for metal casting) obtained by drying or firing the amorphous refractory composition for metal casting of the present invention will be low.If the average fiber diameter exceeds 50.0 μm, the density of the cured product (refractory molded body for metal casting) obtained by drying or firing the amorphous refractory composition for metal casting of the present invention will be low, and the strength of the resulting refractory molded body will be low. The average fiber length of the inorganic fibers is preferably 1 to 200 mm, more preferably 2 to 50 mm, and even more preferably 10 to 50 mm. When the average fiber length of the inorganic fibers is within the above range, it becomes easier to obtain a refractory molded body for metal casting having an appropriate density. In the present application, the average fiber diameter of inorganic fibers means the average value when the diameters of 200 fibers are measured in an image observed by an electron microscope. In the present application, the average fiber length of inorganic fibers means the average value obtained by measuring the fiber lengths of 200 fibers with a vernier caliper.
[0027] The amorphous refractory composition for metal casting according to the present invention contains inorganic fibers in an amount of 1.00 to 15.00 mass %, preferably 1.00 to 12.00 mass %, and more preferably 1.00 to 10.00 mass %, based on the solid content. In the amorphous refractory composition for metal casting of the present invention, since the content ratio of inorganic fibers is within the above-mentioned range, the content of inorganic fibers can be reduced while easily filling the joints and cracks of the refractory body, and the composition itself can be freely shaped and dried and solidified, making it easy to form a refractory body for metal casting that has sufficient strength and erosion resistance for practical use, and has excellent heat retention (insulation) and light weight.
[0028] Since inorganic fibers are lightweight and have low density, when used as a constituent material of a fireproof molding, the mechanical strength is relatively fragile and the fiber is easily corroded by molten metal such as aluminum, etc. However, by using a predetermined amount of inorganic fibers together with an ionic bonding substance and colloidal silica described later as a constituent material of a fireproof molding, a fireproof molding for metal casting can be produced that has sufficient strength and corrosion resistance for practical use, excellent heat retention (insulation), and reduced weight.
[0029] In the amorphous refractory composition for metal casting of the present invention, the organic fiber functions as an aggregate for the amorphous refractory composition, and can be one or more types selected from, for example, natural fibers such as pulp, cotton, hemp, etc., and hydrophobically treated synthetic fibers such as vinylon, rayon, polypropylene (PP), polyethylene (PE), etc.
[0030] In the moldable refractory composition for metal casting according to the present invention, the average fiber diameter of the organic fibers is preferably 1.0 to 50.0 μm, more preferably 5.0 to 30.0 μm, and even more preferably 10.0 to 20.0 μm. If the average fiber diameter of the organic fibers is less than 1.0 μm, the fibers will be prone to breakage, and cracks will be likely to occur in the cured product (refractory molded body for metal casting) obtained by drying or firing the amorphous refractory composition for metal casting of the present invention.If the average fiber diameter of the organic fibers exceeds 50.0 μm, the density of the cured product (refractory molded body for metal casting) obtained by drying or firing the amorphous refractory composition for metal casting of the present invention will be low, and the strength will be likely to be low.
[0031] In the moldable refractory composition for metal casting according to the present invention, the average fiber length of the organic fibers is preferably 1 to 30 mm, more preferably 1 to 20 mm, and even more preferably 2 to 13 mm. If the average fiber length of the organic fibers is less than 1 mm, the amorphous refractory composition for metal casting according to the present invention will be less resistant to pull-out between the organic fibers and the base material during drying or at the beginning of the firing process, and cracks will be more likely to occur. If the average fiber length of the organic fibers exceeds 30 mm, the density of the hardened product (refractory molding for metal casting) obtained by drying or firing will be low, and the bending strength will be more likely to decrease.
[0032] In the present application, the average fiber diameter of organic fibers means the average value when the diameters of 200 fibers are measured in an image observed by an electron microscope. In the present application, the average fiber length of the organic fibers means the average value obtained by measuring the fiber lengths of 200 fibers with a vernier caliper.
[0033] The amorphous refractory composition for metal casting according to the present invention contains organic fibers in an amount of 1.00 to 13.00 mass %, preferably 1.00 to 12.00 mass %, and more preferably 1.00 to 10.00 mass %, based on the solid content. In the amorphous refractory composition for metal casting of the present invention, the content ratio of organic fibers is within the above range, so that the content of inorganic fibers can be reduced while filling the joints and cracks of the refractory body, or the composition itself can be freely shaped and dried and solidified, making it less likely to crack in the hardened product (refractory body for metal casting) obtained by drying or firing. In the amorphous refractory composition for metal casting according to the present invention, depending on the heating temperature during the above-mentioned firing, the organic fibers may completely disappear after the firing process and not remain in the obtained hardened product; however, if no cracks occur during drying or in the initial stage after firing has begun, the occurrence of cracks can be easily suppressed even after firing is completed.
[0034] The amorphous refractory composition for metal casting according to the present invention contains the inorganic fibers and organic fibers in a total amount of 2.00 to 28.00 mass%, preferably 2.00 to 25.00 mass%, and more preferably 8.00 to 11.00 mass%, in the solid content.
[0035] Since the amorphous refractory composition for metal casting of the present invention contains the above-mentioned inorganic fibers and organic fibers in the solid content in the above-mentioned total ratio, the content of inorganic fibers can be reduced while the hardened product obtained by drying or firing is more likely to have a dense structure, making it easy to produce a hardened product (refractory molded body for metal casting) having sufficient bending strength.
[0036] In the amorphous refractory composition for metal casting according to the present invention, the ratio of the content of organic fibers in the solid content to the content of inorganic fibers in the solid content (content of organic fibers in the solid content / content of inorganic fibers in the solid content) is preferably 0.18 to 3.08, more preferably 0.20 to 2.99, even more preferably 0.25 to 2.50, and particularly preferably 0.30 to 2.00, by mass.
[0037] The amorphous refractory composition for metal casting of the present invention contains the above-mentioned inorganic fibers and organic fibers in the solid content in a ratio that satisfies the above-mentioned ratio, so that it is possible to easily produce a hardened product (refractory molding for metal casting) that is less likely to crack and has sufficient bending strength when dried or fired and hardened, while reducing the inorganic fiber content.
[0038] In the amorphous refractory composition for metal casting according to the present invention, the colloidal silica is preferably silica particles or their hydrates dispersed in a colloidal state in water, with a median diameter (D50) of less than 0.10 μm and a 90% cumulative diameter (D90) of less than 0.20 μm, and more preferably a median diameter (D50) of 0.01 μm or more and less than 0.1 μm and a 90% cumulative diameter (D90) of 0.02 μm or more and less than 0.20 μm.
[0039] In the amorphous refractory composition for metal casting of the present invention, colloidal silica imparts sufficient shape retention and strength to the hardened product obtained by drying or firing the amorphous refractory composition for metal casting of the present invention, and exhibits the function of binding inorganic fibers together after hardening, as well as acting as an oxygen source for the molten metal and forming an oxide film of the molten metal (if the metal is aluminum, an aluminum oxide film) at the interface where the hardened product comes into contact with the molten metal. If the colloidal silica has a median diameter (D50) of less than 0.10 μm and a 90% cumulative diameter (D90) of less than 0.2 μm, the surface area of the silica increases after curing, and the oxidation-reduction reaction between the highly reducing molten metal and the silica proceeds quickly, making it easier for an oxide film to form quickly on the refractory surface. On the other hand, if the colloidal silica has a median diameter (D50) of 0.10 μm or more or a 90% cumulative diameter (D90) of 0.20 μm or more, it becomes difficult to form an oxide film quickly, and metals tend to stick to the surface of the resulting cured product.
[0040] The amorphous refractory composition for metal casting according to the present invention can be formed into a desired shape, and then dried or fired to form a hardened product (refractory molded product for metal casting). The hardened product is made of a material containing a predetermined amount of silica and a highly ionic bonding substance described later, and therefore the oxidation-reduction reaction between the molten metal with high reducing power and silica, which is an oxygen source for the molten metal, proceeds quickly, and a metal oxide film can be rapidly formed on the surface of the hardened product. As a result, the metal oxide is formed on the surface of the hardened product before the penetration of the molten metal occurs, so that the adhesion of the metal to the hardened product can be suppressed, and the penetration of the molten metal into the hardened product can be suppressed, and further, the metal oxide itself is easily peeled off, so that damage to the hardened product can be suppressed.
[0041] In the amorphous refractory composition for metal casting according to the present invention, the median diameter (D50) means the diameter of particles that corresponds to 50% of the particle size distribution when calculated from the finest particles, and the 90% cumulative diameter (D90) means the diameter of particles that corresponds to 90% of the particle size distribution when calculated from the finest particles. The particle size distribution of the colloidal silica can be determined by a laser diffraction / scattering method using a nanoparticle size distribution analyzer SALD-7100 (measurement range: 0.01 to 300 μm) (manufactured by Shimadzu Corporation) to calculate the particle size distribution (particle size) from the intensity distribution of light scattered from the particles.
[0042] The amorphous refractory composition for metal casting according to the present invention preferably contains 2.00 to 20.00 mass % of colloidal silica, calculated as silica in the solid content, more preferably 2.00 to 15.00 mass %, and even more preferably 2.00 to 10.00 mass %.
[0043] Colloidal silica is a colloidal substance in which silica particles or their hydrates are dispersed in water, and in the amorphous refractory composition for metal casting according to the present invention, the content of the colloidal silica means the mass proportion, calculated as silica, of the total solid content of the amorphous refractory composition for metal casting according to the present invention.
[0044] If the content of colloidal silica in the solid content is less than 2.00% by mass in terms of silica, the bending strength after curing is likely to be insufficient, whereas if the content of colloidal silica in the solid content is more than 20.00% by mass in terms of silica, the consistency becomes high, the paste-like composition drips during application, and the applied product, such as joints, tends to shrink significantly due to drying.
[0045] In the moldable refractory composition for metal casting according to the present invention, the ionic bonding substance may be one or more selected from calcium fluoride, magnesium fluoride, calcium oxide or its precursor, magnesium oxide or its precursor, barium oxide or its precursor, and barium sulfate. Among the above ionic bonding substances, calcium fluoride is preferred because it has the strongest ionic bonding property.
[0046] An example of the precursor of calcium oxide is calcium carbonate. An example of the precursor of magnesium oxide is magnesium carbonate. An example of the precursor of barium oxide is barium carbonate. These precursors are easily decomposed by heating, so that they are present as calcium oxide, magnesium oxide, and barium oxide, respectively, in the refractory molded body for metal casting after firing.
[0047] The ionic bonding substance has ionic bonding strength equal to or greater than that of the oxide of the molten metal with which it comes into contact, for example, aluminum oxide, and is used for the purpose of forming an oxide film of the molten metal at the interface between the molten metal and the hardened or fired product of the amorphous refractory composition for metal casting according to the present invention. The stronger the ionic bonding property of the ionic bonding substance, the greater the oxide film forming effect, so that even if the content of the ionic bonding substance in the mixture is small, a sufficient oxide film forming effect can be achieved.
[0048] In the amorphous refractory composition for metal casting according to the present invention, the ion-bonding substance preferably has a small particle size, specifically, the average particle size (median diameter (D50)) is preferably 0.15 mm or less, more preferably 0.10 mm or less, and even more preferably 0.050 mm or less. The average particle size (median diameter (D50)) is preferably 0.001 mm or more. When an ionic bonding substance with a small particle size is used, the specific surface area of the ionic bonding substance can be increased overall, so that an oxide film with suitable peelability can be rapidly formed on the surface of the hardened product of the amorphous refractory composition for metal casting according to the present invention.
[0049] In the present invention, the average particle size (median diameter (D50)) of the ionically bonded substance means a value measured by a laser diffraction / scattering method using a nanoparticle size distribution analyzer SALD-7100 (measurement range: 0.01 to 300 μm) (manufactured by Shimadzu Corporation).
[0050] Moreover, it is preferable to use an ion-binding substance having a purity of 90% or more, and it is even more preferable to use an ion-binding substance having a purity of 99% or more.
[0051] The amorphous refractory composition for metal casting according to the present invention preferably contains 4.00 to 40.00 mass %, more preferably 5.00 to 25.00 mass %, and even more preferably 5.00 to 20.00 mass %, of the ion-bonding substance in the solid content.
[0052] In the amorphous refractory composition for metal casting according to the present invention, if the content of the ionic bonding substance in the solid content is less than 4.00% by mass, it becomes difficult to rapidly form an oxide film of the molten metal at the interface where the hardened product of the amorphous refractory composition for metal casting and the molten metal come into contact with each other. Also, if the content of the ionic bonding substance in the solid content exceeds 40.00% by mass, materials with strong ionic bonding generally have a large volume expansion due to heating, so that the thermal shock resistance decreases and the hardened product becomes easily cracked by thermal shock. The amorphous refractory composition for metal casting according to the present invention contains an ionically bonding substance and colloidal silica in a specific ratio, and thus can rapidly form an oxide film of the molten metal at the interface where the resulting hardened material comes into contact with the molten metal. Since this oxide is formed on the surface of the hardened material before the penetration of the molten metal occurs, it is possible to suppress the adhesion of metal to the hardened material, and the penetration of the molten metal into the hardened material is suppressed. Furthermore, since the metal oxide itself is easily peeled off, damage to the hardened material can be easily suppressed.
[0053] The amorphous refractory composition for metal casting of the present invention preferably contains inorganic fibers, organic fibers, colloidal silica and ion-bonding substances in a total amount of 20.00 mass% or more of the total solids, more preferably 25.00 mass% or more of the total solids, and even more preferably 30.00 mass% or more of the total solids.
[0054] In the amorphous refractory composition for metal casting according to the present invention, the inorganic filler is added as an aggregate and may be in the form of particles or needle-shaped material consisting of needle-shaped crystals. In the present application, the inorganic filler does not include the inorganic fibers and ion-bonding substances described above.
[0055] The inorganic filler may be at least one selected from particulate inorganic fillers (particulate matter) and needle-shaped inorganic fillers (needle matter). The particulate inorganic filler (particulate material) may be one or more selected from silica particles, alumina particles, chamotte particles, titania particles, zirconia particles, silicon nitride particles, silicon carbide particles, cordierite particles, and the like. Furthermore, the above-mentioned needle-shaped inorganic filler (needle-shaped material) can be one or more selected from wollastonite, sepiolite, attapulgite, potassium titanate fiber, calcium carbonate fiber, calcium silicate fiber, microfiber cellulose, fibrillated aramid, gypsum, hydromagnesite, etc. As the inorganic filler, a needle-shaped inorganic filler (needle-shaped material) is preferred as described below, and wollastonite is more preferred.
[0056] The amorphous refractory composition for metal casting according to the present invention preferably contains 30.00 to 92.00 mass %, more preferably 40.00 to 90.00 mass %, and even more preferably 50.00 to 80.00 mass %, of the inorganic filler in the solid content.
[0057] The amorphous refractory composition for metal casting of the present invention contains an inorganic filler in the solid content in the above-mentioned range, so that when it is dried or fired and hardened, a dense structure is obtained, and therefore sticking due to penetration of molten metal on the surface of the resulting hardened product (refractory molding for metal casting) can be suppressed.
[0058] The moldable refractory composition for metal casting according to the present invention preferably contains a needle-shaped inorganic filler (needle-shaped objects) such as wollastonite as an inorganic filler. When the amorphous refractory composition for metal casting according to the present invention contains needle-shaped objects as an inorganic filler, the solid content preferably contains 5.00 to 60.00 mass %, more preferably 5.00 to 50.00 mass %, and even more preferably 10.00 to 45.00 mass % of the needle-shaped objects.
[0059] The amorphous refractory composition for metal casting according to the present invention is usually in a paste form containing a desired amount of a liquid medium such as water, and further has a reduced content of inorganic fibers, so that it adheres to the hands and tools of the worker during application and is difficult to peel off, which tends to reduce application and handleability. On the other hand, since the amorphous refractory composition for metal casting according to the present invention contains acicular materials such as wollastonite as at least a part of the inorganic filler in the above-mentioned ratio, the amorphous refractory composition for metal casting is less likely to adhere to the hands or tools used during application, and once adhered, the amorphous refractory composition for metal casting can be easily peeled off, thereby easily improving application and handleability.
[0060] The amorphous refractory composition for metal casting according to the present invention preferably contains inorganic fibers, organic fibers, colloidal silica, ionically binding substances and inorganic fillers in a total amount of 96.0 mass% or more of the total solids, more preferably 97.0 mass% or more of the total solids, and even more preferably 98.0 mass% or more of the total solids.
[0061] The moldable refractory composition for metal casting according to the present invention preferably contains a thickener. In the amorphous refractory composition for metal casting according to the present invention, the thickener is not particularly limited and can be appropriately selected from those commonly used in this technical field, and examples thereof include one or more selected from hydroxyethyl cellulose, sodium acrylate polymer, etc.
[0062] The amorphous refractory composition for metal casting according to the present invention preferably contains 0.01 to 3.00 mass %, more preferably 0.01 to 2.00 mass %, and even more preferably 0.01 to 1.00 mass %, of a thickener in the solid content.
[0063] The amorphous refractory composition for metal casting according to the present invention contains a thickener in the above ratio in the solid content. By containing this component, the consistency of the moldable refractory composition for metal casting according to the present invention can be easily controlled within a desired range.
[0064] The amorphous refractory composition for metal casting according to the present invention comprises inorganic fibers, organic fibers, colloidal silica, an ion-bonding substance, an inorganic filler and a thickener in a total amount of the total solids. It preferably contains 97.0% by mass or more, more preferably 98.0% by mass or more of the total solid content, and even more preferably 99.0% by mass or more of the total solid content.
[0065] The moldable refractory composition for metal casting according to the present invention may contain, in addition to the above-mentioned components, optional components such as a coating layer forming agent, a dispersing agent, and a preservative.
[0066] In the amorphous refractory composition for metal casting according to the present invention, the amorphous shape is not particularly limited. For example, the amorphous shape may be a paste-like shape obtained by mixing a solid component with a liquid medium.
[0067] The liquid medium for forming the paste-like material is not particularly limited, but may be one or more selected from water and polar organic solvents. Examples of the polar organic solvent include monohydric alcohols such as ethanol and propanol, and dihydric alcohols such as ethylene glycol. Of these liquid media, water is preferred in consideration of the working environment and environmental load. The water is not particularly limited, and may be one or more selected from distilled water, ion-exchanged water, tap water, ground water, industrial water, and the like.
[0068] When the amorphous refractory composition for metal casting according to the present invention is in a paste-like form, the viscosity of the paste-like form, i.e., the solids concentration in the liquid medium, is appropriately determined in consideration of the intended use, workability, etc. For example, the content of the liquid medium is preferably 20 to 800 mass%, more preferably 25 to 500 mass%, and even more preferably 30 to 250 mass%, relative to 100 mass% of the solids of the amorphous refractory composition for metal casting according to the present invention. If the content of the liquid medium is less than 20% by mass relative to 100% by mass of the solid matter of the amorphous refractory composition for metal casting according to the present invention, the fluidity of the amorphous refractory composition will be low, leading to poor application properties, and the mechanical strength of the applied product, particularly bending strength, will be easily reduced. If the content of the liquid medium is more than 800% by mass relative to 100% by mass of the solid matter of the amorphous refractory composition for metal casting according to the present invention, the consistency of the amorphous refractory composition will be high, leading to dripping of the paste-like composition during application, and shrinkage of the applied product, such as joints, due to drying will be large. In addition, when calculating the solid content and liquid medium content of the above-mentioned amorphous refractory composition for metal casting, for the colloidal silica used as a component of the amorphous refractory composition for metal casting, the silicon content in the colloidal silica is converted into silica and added to the above-mentioned solid content, and the liquid content (moisture) in the colloidal silica is added to the above-mentioned liquid medium amount, and then the respective amounts are calculated.
[0069] The consistency of the castable refractory composition for metal casting according to the present invention is preferably 100 to 400 (1 / 10 mm), and more preferably 100 to 350 (1 / 10 mm).
[0070] If the consistency is less than 100 (1 / 10 mm), the flexibility of the moldable refractory composition for metal casting is reduced, and the workability is likely to be reduced. If the consistency is more than 400 (1 / 10 mm), the paste-like composition is likely to drip during application, and shrinkage of the applied product, such as joints, due to drying is likely to increase.
[0071] In the present application, the consistency refers to the worked consistency measured according to the JIS K 2220 standard. In other words, when the tip of a standard cone attached to a penetration meter is dropped onto a measurement sample (unshaped refractory composition for metal casting) for only 5 seconds at 25°C in a specified manner, the depth (mm) to which the tip of the standard cone sinks into the measurement sample, i.e., the penetration, is measured, and it means a value 10 times the measured penetration. However, when measuring the above penetration, taking into consideration that it is difficult for the standard cone to penetrate into the measurement sample, the measurement is performed by placing a 150 g weight on the standard cone.
[0072] The consistency of the amorphous refractory composition for metal casting of the present invention can be adjusted and controlled by the amount of liquid excluding solids contained in the amorphous refractory composition for metal casting of the present invention (e.g., the amount of water contained in colloidal silica or the amount of other liquid medium) and the amount of inorganic fibers. Specifically, increasing the amount of the solvent or decreasing the amount of the inorganic fibers increases the consistency, whereas decreasing the amount of the solvent or increasing the amount of the inorganic fibers decreases the consistency.
[0073] The amorphous refractory composition for metal casting according to the present invention is used, for example, as a lining material and joint material for components that come into contact with molten metal, such as gutters, molten metal holding furnaces, and ladles, and can be dried or fired to form a hardened product having any shape.
[0074] Next, a method for producing the castable refractory composition for metal casting according to the present invention will be described. The method for producing the amorphous refractory composition for metal casting according to the present invention can be performed by mixing the above-mentioned inorganic fibers, organic fibers, colloidal silica, ion-bonding substances and inorganic fillers, and, if necessary, further constituent materials such as thickeners, in desired amounts, each calculated as solid matter.
[0075] A preferred method for producing the amorphous refractory composition for metal casting of the present invention is to mix inorganic fibers, organic fibers, ion-bonding substances, and inorganic fillers, as well as other aggregates as necessary, and then add colloidal silica, and further add and mix other compounding ingredients such as a thickener and, if desired, a preservative. Furthermore, when a liquid medium is used, a preferred method is to add inorganic fibers and organic fibers to the liquid medium, then add and mix colloidal silica and an ion-binding substance, and further add and mix other components such as an inorganic filler and a thickener, and if desired, a preservative.
[0076] The amorphous refractory composition for metal casting of the present invention reduces the content of inorganic fibers while increasing the content of organic fibers, and further contains colloidal silica, an ionically bonding substance, an inorganic filler, and a thickener, so that when dried or fired and hardened, it is less likely to crack and forms a hardened product with sufficient bending strength, making it suitable for use as a refractory molding for metal casting.
[0077] Next, the cured product of the moldable refractory composition for metal casting according to the present invention will be described. The cured product of the moldable refractory composition for metal casting according to the present invention is characterized in that it comprises a cured product of the refractory composition for metal casting according to the present invention.
[0078] The details of the castable refractory composition for metal casting, which is a constituent material of the cured product according to the present invention, are as described above.
[0079] The cured product according to the present invention can be easily formed by drying or firing the moldable refractory composition for metal casting according to the present invention.
[0080] The method for producing the cured product according to the present invention includes a method in which the amorphous refractory composition for metal casting according to the present invention is applied or molded by the above-mentioned method, and then dried or fired. A preferred method for producing the cured product of the present invention is to coat or mold the moldable refractory composition for metal casting of the present invention by the above-mentioned method, then dry and then bake the composition.
[0081] When producing the cured product according to the present invention, the drying temperature is preferably room temperature to 180° C., more preferably 40 to 180° C., further preferably 60 to 150° C., and particularly preferably 80 to 120° C. The drying time is preferably 6 to 48 hours, more preferably 8 to 40 hours, and further preferably 10 to 36 hours. The drying atmosphere can be, for example, an air atmosphere, an oxygen atmosphere, or a nitrogen atmosphere.
[0082] When producing the cured product according to the present invention, the baking temperature (baking temperature) is preferably 600 to 1300°C, and more preferably 700 to 900°C. The atmosphere during the firing is not particularly limited, but is preferably an air atmosphere, an oxygen atmosphere, or a nitrogen atmosphere. The firing time is preferably 0.5 to 4 hours. By carrying out the baking treatment, the obtained cured product can be degreased and shrinkage during practical use can be easily prevented.
[0083] As a method for producing the cured product of the present invention, the amorphous refractory composition for metal casting of the present invention may be applied or molded by the method described above, dried, and then the resulting dried product may be used for metal casting purposes (such as by contacting it with molten metal) and subsequently hardened by subjecting it to a firing treatment.
[0084] The amorphous refractory composition for metal casting and its hardened product according to the present invention can be used in areas that come into direct contact with molten metal in casting equipment for aluminum, zinc, magnesium, etc., and although there is no particular limitation on the metal, examples of applications that can be mentioned include aluminum casting and zinc casting.
[0085] According to the present invention, it is possible to provide a cured product of a moldable refractory composition for metal casting that is less susceptible to cracking and has sufficient bending strength while reducing the content of inorganic fibers.
[0086] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples in any way. In the following examples and comparative examples, the following physical properties were measured by the following methods. <Average particle size (median diameter (D50)) and 90% cumulative diameter (D90) of colloidal silica, and average particle size (median diameter (D50)) of calcium fluoride> Each was measured by a laser diffraction / scattering method using a nanoparticle size distribution measuring device SALD-7100 (measurement range: 0.01 to 300 μm) (Shimadzu Corporation). <Consistency> Measurements were made in accordance with the provisions of JIS K 2220. However, taking into consideration the difficulty of inserting the standard cone into the measurement sample, measurements were made with a 150 g weight placed on the standard cone. In the following Examples and Comparative Examples, the paste-like amorphous refractory composition was prepared by kneading a mixture of each component with water using a kneading device such as a kneader or a pressure kneader.
[0087] Example 1 As shown in Table 1, each component was mixed so as to contain 4.34 mass% alumina fiber (Arsen B97 manufactured by Denka Co., Ltd.), 2.17 mass% polypropylene fiber, 6.50 mass% colloidal silica having an average particle size (median diameter (D50)) of 0.02 μm and a 90% cumulative diameter (D90) of 0.04 μm in terms of silica, 18.9 mass% calcium fluoride (average particle size (median diameter (D50)) 45 μm), 42.7 mass% alumina powder, 24.31 mass% wollastonite, 0.64 mass% thickener, and 0.43 mass% preservative, and 29.34 mass parts of water were added to 100 mass parts of solid content in the mixture of each component obtained, and the mixture was kneaded in a kneading device to prepare a paste-like amorphous refractory composition. The mixture of the components before the kneading contains 15.17 parts by mass of water constituting colloidal silica per 100 parts by mass of solids in the mixture of the components. Therefore, the kneading treatment is equivalent to kneading 44.51 parts by mass (15.17 parts by mass + 29.34 parts by mass) of water per 100 parts by mass of solids in the mixture of the components. The consistency of the monolithic refractory composition obtained immediately after the above kneading was 310 (1 / 10 mm).
[0088] The obtained paste-like amorphous refractory composition was filled into a mold, dried at 100°C for 24 hours, and then demolded to obtain a dried body (cured product). The dried body was fired in a heating furnace in an air atmosphere at 700°C for 3 hours to obtain a fired body (cured product). The fired body had a bulk density of 1.28 g / cm 3 The bending strength measured in accordance with the JIS R 2553 standard was 4.82 MPa.
[0089] The obtained paste-like moldable refractory composition was evaluated by the following test methods. The results are shown in Table 1.
[0090] <Cracking test when dry> The obtained paste-like moldable refractory composition was evaluated for the occurrence of cracks at the bent portion when it dried and became a hardened product. First, an L-shaped iron plate having a horizontal portion 200 mm wide and 200 mm long and a vertical portion 200 mm wide and 200 mm long was coated with the obtained paste-like amorphous refractory composition to a thickness of 10 mm on the inner surfaces of the horizontal and vertical portions, and then the composition was air-dried for 5 days to harden. The surface of the obtained hardened product was visually inspected and evaluated as follows: ◯: No cracks were observed on the surface of the obtained cured product. Δ: Cracks were observed on the surface of the obtained cured product, and the arithmetic mean value of the width of the cracks measured at any 10 points with a caliper was 0.1 mm or more and less than 2.0 mm. ×: Cracks were observed on the surface of the obtained cured product, and the arithmetic mean value of the width of the cracks measured at any 10 points with a caliper was 2.0 mm or more.
[0091] <Moldability test> The moldability of the obtained paste-like moldable refractory composition was evaluated by the following methods (1) to (5). (1) The obtained paste-like amorphous refractory composition is measured out into a 90 ml container using a leveller. (2) The paste-like amorphous refractory composition measured in (1) is formed into a sphere and placed in the center of a stainless steel plate measuring 300 mm in length, 300 mm in width, and 3 mm in thickness. (3) A stainless steel plate of the same size as the stainless steel plate is placed on top of the paste-like amorphous refractory composition placed in (2) above, so that the upper and lower stainless steel plates are overlapping each other, thereby sandwiching the paste-like amorphous refractory composition. (4) The stack of two stainless steel plates sandwiching the paste-like amorphous refractory composition obtained in (3) above is roll-pressed once using a roll press under the following conditions: roll diameter 180 mm, roll pressure 0.01 MPa, roll rotation speed 30 rpm, and gap between the upper and lower rolls 13 mm. (5) After the roll pressing in (4), the upper stainless steel plate constituting the laminate of two stainless steel plates is removed, and the area of the main surface of the amorphous refractory composition formed into a flat plate on the lower stainless steel plate is calculated by image analysis. At this time, based on the calculated area value of the main surface, the moldability is evaluated as follows. 〇: Area is 120cm 2 super △: Area is 80cm 2 More than 120cm 2 below ×: Area is 80cm 2 less than
[0092] <Storage test> The obtained paste-like moldable refractory composition was evaluated for whether or not a decrease in consistency occurred during long-term storage. First, the obtained paste-like amorphous refractory composition was stored in a cool, dark place for 6 months after production, and the consistency after 6 months was confirmed and evaluated as follows. ◯: The consistency of the paste-like moldable refractory composition after 6 months is 50% or more of the consistency of the paste-like moldable refractory composition immediately after production. ×: The consistency of the paste-like moldable refractory composition after 6 months is less than 50% of the consistency of the paste-like moldable refractory composition immediately after production.
[0093] <Workability test (hand-release property (hand-attachability) of unformed fireproof moldings)> The obtained paste-like moldable fireproof composition was used for application, and the workability (the releasability (attachability) of the moldable fireproof molding) was evaluated. First, one hand was opened and placed vertically in a container containing the obtained paste-like amorphous fireproof composition while wearing a glove made of natural rubber latex, and was left in that state for 3 seconds. Next, the hand placed in the container was pulled up vertically, and the state of the glove after being pulled up was visually confirmed and evaluated as follows. ◯: The paste-like amorphous fire-resistant composition adheres to the entire glove as powder and is easily removed by shaking the hand. Δ: The paste-like amorphous fire-resistant composition adheres as a powder to the entire glove and also adheres as a sticky substance to some parts between the fingers of the glove. The powdery substance comes off easily by shaking the hand, but the sticky substance hardly comes off at all. ×: The paste-like amorphous fire-resistant composition adheres to the entire glove as a sticky substance, and is hardly removed even when shaken with the hand.
[0094] <Aluminum molten metal immersion test (aluminum molten metal properties)> A rectangular columnar test specimen was formed from the obtained paste-like moldable refractory composition, and the test specimen was immersed in molten aluminum. After the test specimen was pulled out, it was evaluated whether or not the aluminum adhered to the test specimen. First, the obtained paste-like amorphous refractory composition was molded into a rectangular column measuring 200 mm in length, 40 mm in width, and 40 mm in height, and then dried. After that, a rectangular column-shaped test specimen was formed by processing it into a column measuring 160 mm in length, 40 mm in width, and 40 mm in height. Next, aluminum was placed in a crucible-shaped electric furnace and melted by heating at 700°C, and the above-mentioned rectangular columnar test specimen was immersed in the molten aluminum. At this time, the rectangular columnar test specimen was positioned so that the upper surface of the rectangular columnar test specimen was exposed from the surface of the molten aluminum. While the rectangular columnar test specimen was immersed in the molten aluminum, the electric furnace was kept at 700°C, and the test specimen was pulled out 24 hours after the start of immersion, cooled at room temperature, and visually inspected to evaluate it as follows. ◯: No aluminum adhesion was observed on the test specimen. ×: Aluminum sticking to the test specimen was observed.
[0095] (Examples 2 to 32, Comparative Examples 1 to 3) Except for changing the mixing ratio of each component as shown in Tables 1 to 4, a paste-like amorphous refractory composition and its dried body (hardened product) and fired body (hardened product) were produced in the same manner as in Example 1 and evaluated in the same manner as in Example 1. The results are shown in Tables 1 to 4.
[0096] (Reference example 1) As shown in Table 5, aluminosilicate fibers (refractory ceramic fibers (RCF)) were used instead of alumina fibers, and the blending ratios of each component were changed as shown in Tables 1 to 4. Except for this, a paste-like amorphous refractory composition and its dried body (hardened product) and fired body (hardened product) were produced in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The results are shown in Table 5.
[0097] [Table 1]
[0098] [Table 2]
[0099] [Table 3]
[0100] [Table 4]
[0101] [Table 5]
[0102] As can be seen from Tables 1 to 4, the amorphous refractory compositions obtained in Examples 1 to 32 contain, in the solid content, 1.00 to 15.00 mass% inorganic fibers, 1.00 to 13.00 mass% organic fibers, colloidal silica, ionically bonding substances, and inorganic fillers, and therefore are less likely to crack when dried and hardened, and the dried products obtained by firing have bending strength sufficient for practical use. Furthermore, from Tables 1 to 4, it can be seen that the amorphous fireproof compositions obtained in Examples 1 to 32 have excellent moldability, and can therefore be filled into the joints and cracks of fireproof bodies, or can be freely shaped by themselves and then dried and solidified. Therefore, it can be seen that the amorphous refractory compositions obtained in Examples 1 to 32 can be suitably used as amorphous refractory compositions for metal casting, similar to the amorphous refractory molding containing aluminosilicate fibers (refractory ceramic fibers (RCF)) obtained in Reference Example 1.
[0103] On the other hand, from Tables 1 and 2, it can be seen that the amorphous refractory compositions obtained in Comparative Examples 1 to 3 have a content ratio of inorganic fibers or organic fibers in the solid content outside the specified range, and therefore when dried and hardened, they develop large cracks (Comparative Examples 1 and 3), and the moldability and bending strength of the dried product obtained by firing are poor (Comparative Example 2). [Industrial Applicability]
[0104] According to the present invention, an amorphous refractory composition for metal casting is provided which can be filled into joints and cracks in refractory moldings, or can be freely shaped by itself and dried and solidified, while reducing the inorganic fiber content, and which is less likely to crack when dried or fired and hardened to form a hardened product having sufficient bending strength for practical use, and a hardened product of such an amorphous refractory composition for metal casting is also provided.
Claims
1. The solid content contains 1.00 to 15.00 mass % of inorganic fibers, 1.00 to 13.00 mass % of organic fibers, colloidal silica, an ion-bonding substance, and an inorganic filler.
1. A moldable refractory composition for metal casting comprising:
2. The solid content contains 2.00 to 20.00 mass % of the colloidal silica in terms of silica, 4.00 to 40.00 mass % of the ion-binding substance, and The amorphous refractory composition for metal casting according to claim 1, comprising 30.00 to 92.00 mass%.
3. The amorphous refractory composition for metal casting according to claim 1, wherein the solid content contains a total of 2.00 to 28.00 mass% of the inorganic fibers and the organic fibers.
4. The amorphous refractory composition for metal casting according to claim 1, wherein the ratio of the content of the organic fibers to the content of the inorganic fibers in the solid content is 0.18 to 3.08 by mass.
5. 2. The refractory composition for metal casting according to claim 1, wherein said inorganic fibers are alumina fibers.
6. A method for producing the castable refractory composition for metal casting according to claim 1, comprising the steps of: Inorganic fibers, organic fibers, colloidal silica, ion-bonding substances and inorganic fillers, The inorganic fibers are mixed in an amount of 1.00 to 15.00% by mass and the organic fibers are mixed in an amount of 1.00 to 13.00% by mass in the solid content. A method for producing a moldable refractory composition for metal casting, comprising:
7. A cured product of an amorphous refractory composition for metal casting, comprising a cured product of the refractory composition for metal casting according to any one of claims 1 to 5.
Citation Information
Patent Citations
Molded refractory for metal casting, method for manufacturing molded refractory for metal casting, castable refractory composition, and holding member of molten metal for metal casting
JP2011093726A